A clinico-pathological study of benign breast disease at tertiary care centre - Modhia, Dishank; Agarwal, Sanjeev; Yadav, Pawan; Joshi, Arpit (International Surgery Journal, 2022)
Background: Benign breast diseases are 10 times more common than breast cancer in developed countries. It deserves attention because of their high incidence, their impact on women’s life and due to cancerous potential of some histological types. The aim of the study was to evaluate the overall spectrum in relation to age, sex and clinical presentation in a Tertiary care centre. The primary objective of this study was to evaluate and correlate the role of FNAC and histopathological report with clinical examination for differentiating benign and malignant lesion. The secondary objective of this study was to evaluate and correlate the clinico-radiological presentation of the benign breast diseases. Methods: A prospective observational study was conducted at a tertiary care centre where total of 64 patients were taken. Detailed clinical history and examination was done and then compared to histopathological, FNAC, and radiological results. Results: Out of the 61 female patients fibroadenoma was found most common followed by fibrocystic disease and breast abscess. Most common age group was found to be 2nd decade of females having firm, painless swelling as their chief complaints. Accuracy of HPE, radiological and FNAC results were compared with clinical diagnosis. Conclusions: Benign breast diseases are common among young females. Triple assessment is a gold standard approach to breast disease management.